Sosialisasi Kenakalan Remaja dan Bullying Bersama Bhabinkamtibmas di SMPN 4 Pangkalan Kerinci Desa Mekar Jaya, Kecamatan Pangkalan Kerinci, Kabupaten Pelalawan - Supentri, Supentri; Robiyanto, Robiyanto; Husna, Asmaul; Melcin, Sella Angelina; Tamara, Sephia Lisa; Jeni, Frima; Saputri, Aisyah; Amalia, Yessi; Rahmadani, Ardha Laila; Fitri, Alya Syafika; Suraya, Dini (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The socialization of juvenile delinquency and bullying aims to be a form of concern of KukertaMBKM University of Riau students, regarding the problems that are rampant among teenagers. The socialization activities of juvenile delinquency and bullying at SMP 4 Pangkalan Kerinci, Mekar Jaya Village are a form of concern, prevention efforts and to make teenagers aware of how bad the impacts caused by juvenile delinquency and bullying are. Then the process of socialization of juvenile delinquency and bullying at SMP 4 Pangkalan Kerinci, was accompanied by Bhabinkamtibmas Mekar Jaya Village, Mr. Bripka Donal Arifandi. The socialization contains material on Juvenile Delinquency, Bullying, Drugs. Furthermore, a question and answer session was held regarding the socialization material that had been explained by the speaker. The community service activities that were carried out have gone well in accordance with the achievement indicators, that the socialization participants were enthusiastic about the socialization given and actively asked and answered questions about thesocialization material given. This assistance and socialization provide benefits for students to be applied so that they can prevent and reduce the increase in juvenile delinquency in Mekar Jaya Village.